2016
DOI: 10.1108/scm-10-2015-0391
|View full text |Cite
|
Sign up to set email alerts
|

Interplant coordination, supply chain integration, and operational performance of a plant in a manufacturing network: a mediation analysis

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that: • a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
168
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 95 publications
(184 citation statements)
references
References 85 publications
16
168
0
Order By: Relevance
“…machinery, electronics, metal products, transport equipment and motor vehicles industrial sectors). As a result, 7167 companies from the different countries were selected (Cheng et al, 2016 in English, and later translated by national researchers using double-and reverse-translation procedures, in a coordinated manner for countries with similar languages (Vanpoucke et al, 2014).…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
See 4 more Smart Citations
“…machinery, electronics, metal products, transport equipment and motor vehicles industrial sectors). As a result, 7167 companies from the different countries were selected (Cheng et al, 2016 in English, and later translated by national researchers using double-and reverse-translation procedures, in a coordinated manner for countries with similar languages (Vanpoucke et al, 2014).…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…In addition, this research used IMSS data from sixth iteration, ensuring that the IMSS research instruments have already been verified and known to researchers as demonstrated by numerous research publications (e.g. Gimenez et al, 2012;Golini et al, 2014;Chaudhuri and Boer, 2016;Cheng et al, 2016;Chaudhuri et al, 2018) using different versions of the IMSS survey. A common methodology was followed in each country to ensure uniformity in the data collection process.…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations